Hidden allies: how extracellular vesicles drive biofilm formation, stress adaptation, and host–immune interactions in human fungal pathogens - Philipp Brandt; Rima Singha; Iuliana V. Ene (mBio)
ABSTRACT Pathogenic fungi pose a significant threat to human health, especially given the rising incidence of invasive fungal infections and the emergence of drug-resistant strains. This requires the development of vaccines and the advancement of antifungal strategies. Recent studies have focused on the roles of fungal extracellular vesicles (EVs) in intercellular communication and host-pathogen interactions. EVs are nanosized, lipid membrane-bound particles that facilitate the transfer of proteins, lipids, and nucleic acids. Here, we review the multifaceted functions of EVs produced by different human fungal pathogens, highlighting their importance in the response of fungal cells to different environmental cues and their interactions with host immune cells. We summarize the current state of research on EVs and how leveraging this knowledge can lead to innovative approaches in vaccine development and antifungal treatment.